Influence of energy source on early atrial fibrillation recurrences: a comparison of cryoballoon vs. radiofrequency current energy ablation with the endpoint of unexcitability in pulmonary vein isolation. Issue 1 (14th October 2016) - Gunawardene, Melanie A; Hoffmann, Boris A; Schaeffer, Benjamin; Chung, Da-Un; Moser, Julia; Akbulak, Ruken Oezge; Jularic, Mario; Eickholt, Christian; Nuehrich, Jana; Meyer, Christian; Willems, Stephan
Abstract: Introduction: Comparative data of early recurrence rates of atrial fibrillation (ERAF) following second-generation cryoballoon (CB-G2) and radiofrequency current (RFC) ablation for pulmonary vein isolation (PVI) in paroxysmal AF (PAF) are rare. We randomized PAF patients into either PVI with CB-G2 (group 1) or PVI with a combined RFC-approach applying contact force (CF) with the endpoint of unexcitability (group 2) to investigate ERAF. Methods and results: In group 1 ( n = 30), CB-G2-PVI was performed. After CF-PVI in group 2 ( n = 30), bipolar pacing on the ablation line and additional ablation until unexcitability was conducted. Follow-up included 48 h of in-hospital monitoring followed by 5-day Holter ECGs 1, 2, 3, 6, 12 months postablation to evaluate ERAF. Acute PVI was reached in 100% of group 2 and in 99% of group 1. Shorter procedure durations (98.0 ± 21.9 vs. 114.3 ± 18.7 min, P < 0.05) but extended fluoroscopy times (15.4 ± 3.9 vs. 10.0 ± 4.3 min, P < 0.05) were found in the CB-G2 group. Ten non-severe complications occurred (6 vs. 4 in group 1 and 2, P = 0.73). In group 2, five patients suffered from ERAF vs. seven patients in group 1 ( P = 0.67). The time until the occurrence of ERAF was shorter in group 2 (1 day (q1–q3: 1−4.5)) when compared with group 1 (22 (q1–q3: 6−54) days, P = 0.025). Conclusion: ERAF rates were equal among groups; however, they occurred earlier in the initial phase after RFC ablation when compared with CB-G2. PVI utilizing cryoablation is associated with shorter procedure durations but extended fluoroscopy time while being similarly secure.